923. Providers' Perception of CME Antimicrobial Stewardship Quizzes and Its Impact on Antibiotic Prescribing Practices. (15th December 2022) - Chan, Shannon; Harrington, Nicole; Couch, Kimberly A; Marcinak, Rebecca; Shapiro, Craig; Chasanov, William M; Dressler, Robert; Consiglio-Ward, Loretta; Drees, Marci
Abstract: Background: A statewide antimicrobial stewardship (AS) collaborative across 5 health systems was formed with the mission to share best antibiotic prescribing. Recognizing that education is an important pillar of AS intervention, the statewide collaborative implemented a monthly CME quiz focusing on a wide range of clinical infectious diseases and AS topics. These quizzes consisted of 5-10 case-based and clinical pearl questions with evidence-based answers focusing on the adult and pediatric patient populations. Participants were awarded one hour CME credit. After 3 years of distributing the quizzes, we sought to assess the providers' perceptions of the CME quizzes and their impact on clinical practice. Methods: A nine-question survey was emailed to providers, pharmacists, and nurses. Questions regarding providers' perceptions on the importance of antibiotic education and the impact that it has on their clinical practice were included. Results: Among the 89 respondents, 50% were physicians, 25.6% were advanced practice providers, 14% were pharmacists and 3.5% were nurses. The most common practice setting was primary care (43.8%), followed by acute care (35.9%). The monthly ASP quizzes were considered helpful or very helpful in enhancing their practice in 95% of the respondents. More than half of the respondents believed that the ASP quizzes led to enhancement of their ASP knowledge (61.8%). Prescribing shorter duration and narrow spectrum antibiotic were reported by 48 (53.9%) and 28 (31.5%) respondents respectively. Twenty-three (25.8%) respondents reported that they prescribe less antibiotics because of the ASP quizzes and 28 (31.5%) reported that they became more aware of potential harm of antibiotics. The ASP quizzes did not influence, but rather reinforce current prescribing practice in 25% of the respondents. Conclusion: Provider directed education is a core element of both ambulatory and acute care antimicrobial stewardship. Through a statewide initiative, using a monthly CME quiz circulated via email, prescribers were able to improve their knowledge and enhance their prescribing of antibiotics. Most providers perceive this format of education as helpful and describe it as having a positive impact on their prescribing behavior. Disclosures: All Authors : No reported disclosures.